GENDER DIFFERENCES IN USING MOBILE PHONE TOWARD SITUATION AWARENESS AND BRAIN WAVE ACTIVITY - Amelia
Indonesia is one out of ten countries that have the highest accident rate, where 28% of the accidents were experienced by motorcycle users. There were several causes of the accidents, one of them is using mobile phone while driving the motorcycle. This issue is a substantial matter of discussion as there are only few researches that show the study of these matters. Furthermore, previous researches indicate high number of mobile phone user while driving motorcycle and the number difference between male and female driver. Therefore, the purpose of this research is to determine the difference of using mobile phone while driving between male and female motorcycle driver, reviewed by situation awareness and brain wave activity. The methods used to achieve the purpose of this research is by doing observation and experiment. Observation is done by monitoring the behaviour of motorcycle drivers who use mobile phone while driving in Bandung streets. Experiment is implemented by quasi experiment at Bandung Institute Technology university area while maintaining safety aspects and COVID-19 health protocol. There are 24 participants consist of 12 male and 12 female non-academic staff from ITB university. In this research, participants’ situation awareness of using mobile phone while driving is measured by QASA questionnaire, while participants’ brain wave characteristic is studied from the activity of theta, alpha, and beta wave. The activities of mobile phone application are receiving phone call, sending messages, and using GPS. Observation data shows that there are more male motorcycle drivers than female motorcycle drivers that use mobile phone while driving, where male are more likely to be drivers than passengers. Both male and female drivers tend to use the mobile phone for non on-call activity (screen operation) while driving. The QASA questionnaire data also show that there is significant difference between male and female drivers, where male drivers tend to have lower situation awareness than female drivers when replying messages while driving. The brainwave activity data study shows that there is significant difference between male and female alpha brainwave activity, where male drivers have a higher number of alpha brainwave than female drivers when receiving calls, replying messages, and using GPS.